Anticancer Activity of Marine Macroalgae Halimeda tuna from Aceh Waters against Cervical Cancer Cells - Gazali, Mohamad; Husni, Amir; Sukmadewi, Anggris Prasiska; Nurjanah; Nursid, Muhammad; Andriani, Yosie; Zuriat; Hasanah, Uswatun; Syafitri, Rina (Journal of Fisheries and Environment, 2024)
Cancer, as a chronic illness, is characterized by a high mortality rate. Current cancer treatments, such as chemotherapy, have significant drawbacks, including long half-lives and numerous adverse effects. Medications derived from natural products offer a safer alternative as supplementary treatments. One such natural product is marine macroalgae, commonly known as seaweed. Secondary metabolites from marine macroalgae exhibit a range of potential biological activities, including anticancer properties. The objective of this study was to determine whether the methanolic extract of Halimeda tuna from the Acehnese coast possesses potential anticancer properties. Halimeda tuna was extracted using the cold maceration process, which involved immersion in methanol solvent for 24 h. The MTT assay was used to assess the cytotoxicity of crude H. tuna extract against HeLa cervical cancer cells. GC-MS testing and phytochemical analysis were conducted to identify the compounds present in the extract. The yield of H. tuna extract was 0.168±0.025%. The MTT assay determined the IC50 value of H. tuna against HeLa cells to be 126.460±46.167 µg·mL-¹. Phytochemical analysis revealed the presence of flavonoids, steroids, and alkaloids, while GC-MS analysis identified fatty acids, steroids, and flavonoids in the extract. These compounds may contribute to the anticancer effects observed, consistent with an IC50 value that indicates moderate cytotoxicity. Further research is required to explore the potential of H. tuna extract as an alternative anticancer agent.